BA 101 - Introduction to Business - Linn Benton Virtual College (2018)
This course provides a general survey of the functional and interdependent areas of business management, marketing, accounting and finance, and management information systems. The course includes business trends, operation and management of a business, ethical challenges, environmental responsibility, change, global perspectives, and the dynamic roles of management and staff. Additionally, the course incorporates aspects of team interaction and continuous process improvement. You are provided with the opportunity to explore the Internet and information technology relating to business operations.